Effects of water quality in oil palm production landscapes on tropical waterbirds in Peninsular Malaysia. Issue 5 (4th August 2015) - Sulai, Petra; Nurhidayu, Siti; Aziz, Najjib; Zakaria, Mohamed; Barclay, Holly; Azhar, Badrul
Abstract: Oil palm expansion is a major driver of habitat loss in the tropics. Although a number of studies have evaluated the consequences for terrestrial biodiversity, the effects on wetland habitats and fauna are less well described. This study aims to determine the conservation value of flood‐control drainage channels in oil palm smallholdings for waterbirds. We also measured the water quality (water temperature; pH; dissolved oxygen, DO; total dissolved solids, TDS; salinity; water depth; conductivity; and turbidity) and habitat characteristics (vegetation cover and channel width) to determine the relationship between waterbird species richness, water quality, and habitat characteristics. Birds were surveyed along 25 line transects within peat swamp‐ and mangrove‐converted oil palm smallholdings. Data were collected in seven smallholdings between March and December 2013. We recorded a total of 1111 waterbirds from eight resident species. Both mangrove forest‐ and peat swamp‐converted smallholdings had similar waterbird diversity. Waterbird species richness increased with increasing DO and decreased with water depth, temperature, and conductivity. The most parsimonious predictive model (minimum quasi Akaike information criterion = 476.48) explained 52.39 % of the variation in species richness. Our data indicate that even man‐made aquatic habitats, such as flood‐control channels, can be important for some waterbirds in oil palm smallholdings. However, considering the relatively small increase in waterbird species richness in channels, the most successful strategy for conserving waterbirds will require protection of intact wetlands supported by better management of drainage channels in oil palm smallholdings.